Partial Conservation between Mice and Humans in Olfactory Bulb Interneuron Transcription Factor Codes - Fujiwara, Nana; Cave, John W. (Frontiers in Neuroscience, 2016)
The mammalian main olfactory bulb (OB) has a large population of GABAergic inhibitory interneurons that contains several subtypes defined by the co-expression other neurotransmitters and calcium binding proteins. The three most commonly studied OB interneuron subtypes co-express either Calretinin, Calbindin, or Tyrosine hydroxylase (Th). Combinations of transcription factors used to specify the phenotype of progenitors are referred to as transcription factor codes, and the current understanding of transcription factor codes that specify OB inhibitory neuron phenotypes are largely based on studies in mice. The conservation of these transcription factor codes in the human OB, however, has not been investigated. The aim of this study was to establish whether transcription factor codes in OB interneurons are conserved between mice and humans. This study compared the co-expression of Foxp2, Meis2, Pax6 and Sp8 transcription factors with Calretinin, Calbindin, or Th in human and mouse OB interneurons. This analysis found strong conservation of Calretinin co-expression with Sp8 and Meis2 as well as Th co-expression with Pax6 and Meis2. This analysis also showed that selective Foxp2 co-expression with Calbindin was conserved between mice and humans, which suggests Foxp2 is a novel determinant of the OB Calbindin interneuron phenotype. Together, the findings in this study provide insight into the conservation of transcription codes for OB interneuron phenotypes between humans and mice, as well as reveal some important differences between the species. This advance in our understanding of transcription factor codes in OB interneurons provides an important complement to the codes that have been established for other regions within the mammalian central nervous system, such as the cortex and spinal cord.